Extrafloral nectary morphology and the role of environmental constraints in shaping its traits in a common Cerrado shrub (Maprounea brasiliensis A. St.-Hill: Euphorbiaceae) - Delgado, Marina Neves; Bao, Sonia Nair; Amaral, Lourdes I. V.; Rossatto, Davi Rodrigo [UNESP]; Morais, Helena Castanheira de (Soc Botanica Sao Paulo, 2014)
This study aimed to elucidate the anatomy and morphology of extrafloral nectaries (EFNs) in Maprounea brasiliensis and whether environmental factors influence their traits of production and morphology. For this reason, we sampled leaves from individuals subjected to distinct fire and water regimes, and the anatomy and ultrastructures of EFNs as well as the chemical constitution of nectar were analyzed. EFN nectar production was associated with immature and recently expanded leaves. EFNs originate from the epidermis. At the end of ontogeny, secretory cells are surrounded by three or more layers of cells with secondary and lignified walls, isolating the EFN of vascular tissue. The ultrastructural analysis revealed mature EFNs with secretory activity. The experiments showed that EFN production was not influenced by the presence of frequent fires. However, during the rainy season, new produced leaves had nectaries in greater quantity and diameter than leaves produced during the dry season. The anatomical and ultrastructural changes demonstrated that nectar production is strongly influenced by the age of the nectaries which influence ant attendance to EFN since no ants were observed on leaves that did not secrete nectar. The seasonality experiment confirmed that EFNs of M. brasiliensis are resource dependent and evolutionary programed to appear in elevated number during the rainy season.
Keywords: Anatomy; Frequent fire; Nectar; Seasonality effects; Ultrastructure